1996
DOI: 10.1055/s-2007-1011988
|View full text |Cite
|
Sign up to set email alerts
|

The Extended Transseptal Approach in Complex Mitral Valve Surgery - Evaluation of Risks and Benefits

Abstract: The extended transseptal approach to the mitral valve was used in 32 patients undergoing isolated or combined mitral valve surgery. In all cases exposure of the entire mitral valvular apparatus was excellent. Two patients died of low output within 30 days of surgery. No cause of death was related to the extended transseptal approach. In one early patient reexploration revealed arterial bleeding from the right atrial suture line which was caused by damage to the sinus nodal artery. In 7 patients temporary atria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…[1][2][3][4][5]9,10 Our results showed that although the operative field was smaller than that of the classic approach, the modified approach was always closer to the edge of the mitral valve, so its exposure was relatively simple in all cases. Furthermore, closure after this approach was much simpler than after the classic approach.…”
Section: Discussionmentioning
confidence: 67%
See 2 more Smart Citations
“…[1][2][3][4][5]9,10 Our results showed that although the operative field was smaller than that of the classic approach, the modified approach was always closer to the edge of the mitral valve, so its exposure was relatively simple in all cases. Furthermore, closure after this approach was much simpler than after the classic approach.…”
Section: Discussionmentioning
confidence: 67%
“…This modified approach does not cut through the right atrial appendage and part of the right atrium, therefore, although it may damage the superior right atrial artery (one blood source for the sinus node) and bundle branches, it can better nourish the sinus region from the collateral system around the sinus node, and increase the number of atrial muscle fibers that connect the sinus node with the atrioventricular node, thus reinforcing sinoatrial conduction. 1 5,9,10 Our results showed that although the operative field was smaller than that of the classic approach, the modified approach was always closer to the edge of the mitral valve, so its exposure was relatively simple in all cases. Furthermore, closure after this approach was much simpler than after the classic approach.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation